2018
DOI: 10.1021/acsami.8b17604
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Synthesis of Gel Glass Embedded with Luminescent Silicon Nanoparticles

Abstract: Preparation of highly luminescent glasses involves expensive and complicated processes and usually requires high temperature. In this work, we show that luminescent silicon (Si) nanoparticle (NP)-embedded silicate gel glasses can be developed under near-ambient conditions by a remarkably simple, one-pot strategy, without using any sophisticated instrumentation or technique. Simultaneous hydrolysis and reduction of (3-aminopropyl)triethoxysilane leads to the formation of colloidal Si nanocrystals that can be tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Structural defects and dangling OH – bonds act as and limit the quantum yield of the nanoparticles. This is comparable to and even better than some other luminescent nanoparticles. …”
Section: Resultsmentioning
confidence: 54%
“…Structural defects and dangling OH – bonds act as and limit the quantum yield of the nanoparticles. This is comparable to and even better than some other luminescent nanoparticles. …”
Section: Resultsmentioning
confidence: 54%
“…The absorption peak at 958 cm –1 corresponds to the Si–OH group of APTES. Furthermore, examination of Figure d showed that the two peaks in Si NPs merged into a single broad band at 1031 cm –1 , which is a typical Si–O–Si/SiO corresponding band. The presence of a characteristic absorption broad peak in p-Si NPs can be observed (orange shadow), further indicating that the silicon-based nanoparticle composite polymer is successfully synthesized. The absorption peak near 3500 cm –1 corresponds to the tensile vibration of some free groups −OH and –NH, and the hydrogen bond generated by intermolecular association will make the stretching vibration frequency move to the low wavenumber direction, and the peak deformation is wide.…”
Section: Resultsmentioning
confidence: 94%
“…Synthesis of Si NCs. Si NCs were synthesized by simultaneous hydrolysis and reduction of (3-aminopropyl) triethoxysilane (APTES) by sodium ascorbate (SA) at room temperature under continuous magnetic stirring [50]. Reduction of the alkoxysilane coupling reagent (APTES) generates crystalline Si nuclei which are then driven to form small NCs in the well-known nucleation growth process.…”
Section: Methodsmentioning
confidence: 99%
“…It takes barely 30 min to complete the whole process of synthesis of colloidal Si NCs. The surfaces of the NCs are covered with numerous hydrophilic amino groups which makes the Si NCs water dispersible [50]. The colloidal Si NCs exhibit intense room temperature PL and the fluorescence intensity remains more-or-less same even after irradiation of the sample for 60 min with 30 mW (390 nm) UV as shown in figure S1, which is available online at stacks.iop.org/SST/35/035003/mmedia (section S1, supporting information), suggesting good photostability of the sample.…”
Section: Methodsmentioning
confidence: 99%